Correlation Modes Initial Setting Investigation-Based Group Inquiry Model Formulating Grant Hypotheses Against Student Ability in Science Skills - Sinuraya, Jurubahasa; K, Abdul Hamid; Napitupulu, Efendi (Advances in Social Sciences Research Journal, 2021)
In the implementation of experimental activities, the competence that is expected to be mastered by a student is to appreciate the various concepts and principles of advanced physics by conducting various physics experiments and being able to develop creativity in designing experiments. Physics lessons are subjects related to numbers and some abstract concepts. The study aims to determine the correlation of the Initial Setting variable (X) of the Investigation-Based Group Inquiry Model to the science process skills variable (Y). Data analysis used a single linear regression correlation test using SPSS. The research sample was physics students. The data analysis technique used in this research is the statistical analysis technique of quantitative data calculations. The results of the analysis for the coefficient of determination R Square of 0.251 indicate that 25.1% of science process skills have a direct effect by the Initial Setting (X) variable of the Investigation-Based Group Inquiry Model.